2014
DOI: 10.2105/ajph.2013.301852
|View full text |Cite
|
Sign up to set email alerts
|

From the Sidelines to the Frontline: How the Substance Abuse and Mental Health Services Administration Embraced Smoking Cessation

Abstract: Smoking is a major contributor to premature mortality among people with mental illness and substance abuse. Historically, the Substance Abuse and Mental Health Services Administration (SAMHSA) did not include smoking cessation in its mission. We describe the development of a unique partnership between SAMHSA and the University of California, San Francisco’s Smoking Cessation Leadership Center. Starting with an educational summit in Virginia in 2007, it progressed to a jointly sponsored “100 Pioneers for Smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
(3 reference statements)
0
15
0
Order By: Relevance
“…Another recent study found that having financial resources specifically dedicated to tobacco cessation predicted programs’ adoption of tobacco cessation counseling and pharmacotherapy services (Eby et al, 2015). Similarly, leadership has been identified as a cornerstone of implementing organizational change to promote tobacco cessation (Santhosh et al, 2014; Ziedonis et al, 2006). Respondents in our study referred to enhanced training of existing staff, and also commented on the potential advantages of trained peer mentors.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study found that having financial resources specifically dedicated to tobacco cessation predicted programs’ adoption of tobacco cessation counseling and pharmacotherapy services (Eby et al, 2015). Similarly, leadership has been identified as a cornerstone of implementing organizational change to promote tobacco cessation (Santhosh et al, 2014; Ziedonis et al, 2006). Respondents in our study referred to enhanced training of existing staff, and also commented on the potential advantages of trained peer mentors.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of that shift are the movement of state psychiatric hospitals in the U.S. from 20% smoke‐free in 2005 to 83% by 2011; the increasing use of telephone quitlines by smokers with mental health conditions; and the actual or pending adoption of smoking cessation as a core policy by professional and advocacy organizations such the American Psychiatric Nurses Association, the American Psychiatric Association, the American Psychological Association, and the National Alliance for Mental Illness. In addition, the Substance Abuse and Mental Health Services Administration, the largest U.S. federal agency focused on behavioral health clients, has integrated smoking cessation into its core goals.…”
mentioning
confidence: 99%
“…Therefore it is important that community mental health therapists understand the epigenetic of addictions, to be able to tailor a personalized treatment plan that meets the unique needs that are brought at the therapeutic table [8]. Santhoush et al [9], agreed that addiction is an emotion-cognitive-physiological state that alters behavioral and emotional-cognitive capacities of functioning, as the person' well-being become more dependent on the amount of mental or mood-altering addictive substances. Notable is the fact that one does not need to rely daily on the addictive substances to reach a state of addiction.…”
mentioning
confidence: 99%
“…On the other hand, one may find difficult to return to the abstinence path and continues to resort to the compulsive use of addictive substances, slowly down spiraling in the persistent and dysfunctional patterns of addiction to the point that sober living is incompatible to the daily functioning. At this point, one reached a chronic compulsively dependent state that is fatal if left untreated, and in this is the stage one comes to seek help from the community mental health addiction therapist, alone, or with a family member, or because of legal issues, one may have at that time [8,9]. The addiction therapist engages one in various therapies such as Cognitive Behavioral Therapies (CBT), Motivational Interviewing (MI), Solution-Focused Therapy (SFT), Dialectical Behavioral Therapy (DBTA), and Trauma-Based Therapies (TBT), [8].…”
mentioning
confidence: 99%